Interprofessional collaboration in nursing homes (interprof): a grounded theory study of general practitioner experiences and strategies to perform nursing home visits - Fleischmann, Nina; Tetzlaff, Britta; Werle, Jochen; Geister, Christina; Scherer, Martin; Weyerer, Siegfried; Hummers, Eva; Müller, Christiane Annette (BMC family practice, 2016)
Interprofessionalism, considered as collaboration between medical professionals, has gained prominence over recent decades and evidence for its impact has grown. The steadily increasing number of residents in nursing homes will challenge medical care and the interaction across professions, especially nurses and general practitioners (GPS). The nursing home visit, a key element of medical care, has been underrepresented in research. This study explores GP perspectives on interprofessional collaboration with a focus on their visits to nursing homes in order to understand their experiences and expectations. This research represents an aspect of the interprof study, which explores medical care needs as well as the perceived collaboration and communication by nursing home residents, their families, GPS and nurses. This paper focusses on GPS' views, investigating in particular their visits to nursing homes in order to understand their experiences. Methods: Open guideline-interviews covering interprofessional collaboration and the visit process were conducted with 30 GPS in three study centers and analyzed with grounded theory methodology. GPS were recruited via postal request and existing networks of the research partners. Results: Four different types of nursing home visits were found: visits on demand, periodical visits, nursing home rounds and ad-hoc-decision based visits. We identified the core category "productive performance" of home visits in nursing homes which stands for the balance of GPŚ individual efforts and rewards. GPS used different strategies to perform a productive home visit: preparing strategies, on-site strategies and investing strategies. Conclusion: We compiled a theory of GPS home visits in nursing homes in Germany. The findings will be useful for research, and scientific and management purposes to generate a deeper understanding of GP perspectives and thereby improve interprofessional collaboration to ensure a high quality of care.